Modifiers of GRN-Associated Frontotemporal Lobar Degeneration. Issue 10 (October 2017) - Wauters, Eline; Van Mossevelde, Sara; Van der Zee, Julie; Cruts, Marc; Van Broeckhoven, Christine
Abstract : Heterozygous loss-of-function (LOF) mutations in the human progranulin gene ( GRN ) cause frontotemporal lobar degeneration (FTLD) by a mechanism of haploinsufficiency. Patients present most frequently with frontotemporal dementia, which is the second most common neurodegenerative dementia at young age. Currently, no disease-modifying therapies are available for these patients. Stimulating GRN protein expression or inhibiting its breakdown is an obvious therapeutic strategy, and is indeed the focus of current preclinical research and clinical trials. Multiple studies have demonstrated the heterogeneity in clinical presentation and wide variability in age of onset in patients carrying a GRN LOF mutation. Recently, this heterogeneity became an opportunity to identify disease modifiers, considering that these might constitute suitable targets for developing disease-modifying or disease-delaying therapies. Trends: Heterozygous LOF mutations in GRN leading to GRN protein haploinsufficiency are a major cause of FTLD. Ongoing preclinical research and clinical trials are focused on therapies to increase GRN levels or to inhibit its breakdown. Patients carrying a causal GRN mutation, display phenotypic and age of onset heterogeneity. SORT1, PSAP, and RIPK1 have been identified as modifiers of GRN levels. Variations in TMEM106B have been identified as a risk factor for FTLD-TDP, with a strong effect in GRN mutation carriers. Research into onset age modifiers of FTLD has intensified. These modifiers are potential targets for disease-modifying therapies, which are currently not available.